Nitrogen management for grain yield and protein in the Northern Great Plains. Issue 5 (21st September 2015) - Jones, Clain; Olson-Rutz, Kathrin
Abstract : The single most important thing a grower can do to get record wheat yields is improve nitrogen (N) management.1 Optimum N management for increased grain yield and protein includes: basing N rates on realistic yield potential, knowing the soil residual N, determining application rate and timing, and using appropriate placement and N sources. The steps are the same for all regions, but decisions should be based on guidelines specific to a grower's area. Earn 1 CEU in Nutrient Management by reading this article and taking the quiz at www.certifiedcropadviser.org/certifications/self‐study/724